Wave disturbances over east China Sea (AMTEX area) during AMTEX 75 (MAUSAM, 1980)
In order to understand different aspects of AMTEX 75, heat and moisture budgets over AMTEX area for AMTEX 75 were estimated earlier (Krishna Murty, 1976). In continuation of that study, in the present paper the characteristics of the wave disturbances that appeared in AMTEX 75 are studied. Though the AMTEX 75 period is only the latter half of February 1975, for better understanding, analysis of the data is done for the complete months of February and March 1975 separately.The wave disturbances of both the months are studied for 2 different regions zone-I and zone-11 along latitudes 30 to 32 deg. N and 24 to 26 deg. N respectively. In February, the wave disturbances are of 2-3 day period in both the regions. But, in March there exists a wave disturbance of 3-day period in the north (zone-I) while in the south (zone-II) there exists a disturbance with 5-day period.The disturbances have the characteristics of propagating eastwards, and their wavelength is about 4000 to 5000 km. The vertical structure of these disturbances is same as those of baroclinic waves with warm and moist air to the east of the trough and the trough tilting westwards with height. The change of these characteristics takes place after a certain height, above which the trough tilts eastwards with height and the air to the east of the trough becomes cold and dry. Though the change in the tilting of the trough takes place at a greater height the change in the characteristics of the air to the east of the trough takes place at a much lower level. Interestingly, the changing level is lower over continent than over sea. It may be due to the/difference in the low lying boundary in both the cases.The vertical velocities are computed for a square area and a triangle area and their power spectral distribution is also studied. It is, noticed that the power density increases as the waves move eastwards.